2012
DOI: 10.1186/1476-069x-11-s1-s11
|View full text |Cite
|
Sign up to set email alerts
|

Bladder cancer, a review of the environmental risk factors

Abstract: BackgroundMany epidemiological studies and reviews have been performed to identify the causes of bladder cancer. The aim of this review is to investigate the links between various environmental risk factors and cancer of the bladder.MethodsA systematic literature search was performed using PubMed, Science Direct, Scopus, Scholar Google and Russian Google databases to identify reviews and epidemiological studies on bladder cancer risk factors associated with the environment published between 1998 and 2010. Only… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
148
0
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 226 publications
(168 citation statements)
references
References 41 publications
4
148
0
4
Order By: Relevance
“…The contribution of CYP1 family (CYP-1A1, 1A2, and 1B1) mediated oxidation of xenobiotics including polycyclic aromatic hydrocarbons and aromatic amines to mutagenic and carcinogenic metabolites is well established (4). This is pertinent to bladder cancer in which there is a strong epidemiologic association between development of this neoplasia and exposure to aromatic amines either from cigarette smoke or occupational exposure (5). This is supported by a study of human exfoliated urothelial cells, which has shown that CYP1A1 protein was expressed in a significantly greater proportion of cells from tobacco smokers than nonsmokers (6).…”
Section: Introductionmentioning
confidence: 99%
“…The contribution of CYP1 family (CYP-1A1, 1A2, and 1B1) mediated oxidation of xenobiotics including polycyclic aromatic hydrocarbons and aromatic amines to mutagenic and carcinogenic metabolites is well established (4). This is pertinent to bladder cancer in which there is a strong epidemiologic association between development of this neoplasia and exposure to aromatic amines either from cigarette smoke or occupational exposure (5). This is supported by a study of human exfoliated urothelial cells, which has shown that CYP1A1 protein was expressed in a significantly greater proportion of cells from tobacco smokers than nonsmokers (6).…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we sought to examine the incidence of LUTS without hematuria as an initial presenting symptom for bladder cancer in a high risk population, namely an elderly (2), veteran (8), male (2) cohort with significant tobacco (9) and chemical/environmental (10) exposures. Further, we sought to compare the clinical and pathologic data between patients who presented with LUTS compared to those who presented with gross or microscopic hematuria.…”
Section: Introductionmentioning
confidence: 99%
“…naphthalene, benzo(a)pyrene), coal tar, aniline pigments (e.g. methoxyaniline, methoxy-nitroaniline), polychlorinated dibenzodioxins, dibenzofuran, and chlorinated aliphatic hydrocarbons [7,17,18]. A major role is also played by metals such as arsenic, cadmium, chromium, and nickel [18].…”
Section: Occupational Factorsmentioning
confidence: 99%
“…2-naphthylamine, 4-aminobiphenyl, 4-nitrobiphenyl, benzidine, aniline pigments, soot), and factors related to diet and lifestyle (fluid intake, calorie intake, fat content in diet). A diet rich in fruits, vegetables, and polyphenols found in green tea, as well as vitamins and minerals is generally considered as a positive lifestyle factor [6,7].…”
Section: Introductionmentioning
confidence: 99%